2013
DOI: 10.1016/j.tics.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Why skill matters

Abstract: Maximizing rewards per unit time is ideal for success and survival for humans and animals. This goal can be approached by speeding up behavior aiming at rewards, and this is done most efficiently by acquiring skills. Importantly, reward-directed skills consist of two components: finding a good object (object skill) and acting on the object (action skill), which occur sequentially. Recent studies suggest that object skill is based on high capacity memory on object-value association. When a learned object appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 109 publications
4
77
0
3
Order By: Relevance
“…When you encounter a good (high-valued) object, you will orient your gaze by making a saccadic eye movement to the object and probably approach it (Awh et al 2012; Tatler et al 2011). This value-based orienting is universal among animals (Bromberg-Martin et al 2010) and crucial for survival (Hikosaka et al 2013). Indeed, gaze (or attention) is strongly attracted by objects with high reward values and this fundamental decision making is regulated by the CD, as shown in the following sections.…”
Section: Differential Value Coding In Caudate Nucleusmentioning
confidence: 99%
See 2 more Smart Citations
“…When you encounter a good (high-valued) object, you will orient your gaze by making a saccadic eye movement to the object and probably approach it (Awh et al 2012; Tatler et al 2011). This value-based orienting is universal among animals (Bromberg-Martin et al 2010) and crucial for survival (Hikosaka et al 2013). Indeed, gaze (or attention) is strongly attracted by objects with high reward values and this fundamental decision making is regulated by the CD, as shown in the following sections.…”
Section: Differential Value Coding In Caudate Nucleusmentioning
confidence: 99%
“…Indeed, the categorization or identification of visual objects that requires long-term learning is performed subconsciously (Chun & Jiang 1998; Shiffrin & Schneider 1977; Sigman & Gilbert 2000). Lastly, the quick and automatic response based on stable values is an essential skill to survive in the competitive world (Hikosaka et al 2013). …”
Section: Memories Required For the Stable Value Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, motor skill learning is accompanied by a shift in the speed-accuracy trade-off curve (Willingham 1998;Krakauer and Mazzoni 2011;Shmuelof and Krakauer 2011) which allows movements to occur faster with both increased accuracy (Fitts 1954;Reis et al 2009;Dayan and Cohen 2011) and reduced variability (Shmuelof et al 2012). These characteristics indicate an evolutionary role of motor skill learning in maximizing rewards through faster and more accurate goal-directed movements (Crossman 1958;Shadmehr 2010;Hikosaka et al 2013). Some human studies have shown that rewards can have profound effects on motor skill learning (Johannsen 1962;Sugawara et al 2012;Wulf et al 2014) and performance vigor (Meyniel and Pessiglione 2014), which was even reflected in corticospinal excitability (Klein et al 2012b).…”
mentioning
confidence: 99%
“…Also, it has, for instance, been observed that, as a behavior is repeated, certain motor--related neural activities become more probable under certain conditions (e.g., Costa 2007;Wickens et al 2007;Graybiel 2008;Verstynen & Sabes 2011;Hikosaka et al 2013;Kim et al 2015;Anderson 2016). together are subsequently more likely to be active together under certain conditions, and vice versa (e.g., Hebb 1949;Klaes et al 2012). These changes can happen rapidly (within milliseconds), and involve intracellular biochemical changes which influence synaptic transmission among other things (e.g., Friedman et al 2015;Cichon and Gan 2015;Svensson et al 2016).…”
Section: The Wild Coincidence Objection: An Empirical Objection Withomentioning
confidence: 99%